Adoption of SNI ISO/IEC 17025:2017 Principles for Laboratory Management Information System Development - Gilbert Frans Wijaya; Nabila Rizky Oktadini; Putri Eka Sevtiyuni; Muhammad Ali Buchari (ULTIMA InfoSys, 2022)
— The Software Engineering and Information System Laboratory of Sriwijaya University is in charge of building a technology-based system, in accordance to the strategic objectives of Sriwijaya University which prioritizes the principles of Good governance. To support laboratory operations, a management information system is needed to improve efficiency in planning, managing and reporting. The purpose of this research is to develop a laboratory management information system that adheres to the principles in the SNI ISO/IEC 17025:2017 standard. The software was developed using the Framework for the Application System Thinking (FAST). In the requirement analysis phase, an in-depth study was carried out to formulate requirements in accordance with the principles in the SNI ISO/IEC 17025:2017 clause control standard. In the end, a Laboratory MIS was successfully developed using this approach. It improves laboratory performance, so that capable to provide better services